MERITOKRASI SEBAGAI RESOLUSI ANTI-NEPOTISME PMII: Sintetis Maqāṣid Al-Qur’ān Induktif dan Analisis Framing Digital - Atoillah, Muhammad Agil Atoillah; Muhammad Luthfi Syarif; Muhammad Sheva Firmansyah (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
Widespread nepotism within student organizations, particularly PMII, has become a serious ethical and structural challenge, threatening the principles of meritocracy and internal justice. This phenomenon has become increasingly prominent as it has been critically highlighted through digital platforms that demand a theological-normative response and transformative solutions. Therefore, this study aims to integrate a thematic interpretation of the principles of justice in the Qur’ān with an analysis of the framing patterns of the issue of nepotism by a specific digital account; @a.nande_, to formulate an adaptive socio-meritocratic resolution. This study uses a qualitative approach with a library research framework, applying inductive Waṣfī ‘Āshūr Maqāṣid analysis to complement the ‘framing solution’ of anti-nepotism values (ḥifẓ al-kifāyah), as well as Robert M. Entman’s framing model analysis to dissect the construction of public opinion. The results of the study show that the discourse on nepotism in PMII is strongly framed in the digital space by emphasizing Diagnosis Causes and Moral Evaluation, which is normatively contrary to the distributive justice of the Qur’ān. This study concludes that resolving the problem of nepotism requires strengthening a transparent meritocracy system and utilizing social media as an instrument of moral policing and a catalyst for organizational reform.